Analysis and Detection of Fingerprint Patterns Across Three Generations in Families of the Vidarbha Region Population - Abhaya A Bhople; Khushboo D Bhoyar; Mangesh S Dhore; Radha S Tamgire; Anjali P Ghorpade; Bhagyashree S Ghodeswar (International Journal of Genetic Modifications and Recombinations, 2026)
Fingerprint patterns are unique and reliable for identification. This study focuses on a comparative analysis to determine the inheritance of fingerprint patterns across three generations in families of the Vidarbha region population. The sample collection process for this comparative analysis involved working with 100 families. The study aims to gain insights into the hereditary aspects of fingerprint characteristics among three generations. The research methodology involves the collection of fingerprint samples which were taken by ink and roll method and the analysis of patterns using magnifying lenses. The results reveal that there may be a possibility of genetic influence and concordance in fingerprints patterns, contributing to our understanding of dermatoglyphics. The study indicates a strong hereditary influence on fingerprint patterns across three generations. The research has implications for transmission of fingerprint pattern, genetics and personal identification.
Keywords: Concordance; Dermatoglyphics; Fingerprint Patterns; Inheritance; Magnifying lenses